Assessment of Associated Factors of Low Birth- Weight Babies - Sabnis, Sharad Panditrao; Undari, N Uma (Asian Journal of Medical Research, 2021)
Background: Low birth weight is one of the most serious challenges in maternal and child health in both developed and developing countries. The present study was conducted to assess prevalence of low- birth weight babies. Subjects and Methods: 120 babies of both genders were included. Parameters such as feeding practices, birth weight, family type, anaemic status of mother, ANC, period of gestation and anthropometric measurement was recorded. Infant with a birth weight < 2500 grams were considered low birth weight. Results: Age group <1 month had 28, 1-6 months had 72 and 6-12 months had 20 babies. The difference was significant (P< 0.05). There were 80 low birth weight and 40 normal birth weight babies. Among low birth weight, 5 were normal, 28 had grade 1, 22 had grade 2, 15 had grade 3 and 10 had grade 4. Among normal birth weight, 17 were normal, 7 had grade 1, 6 had grade 2, 8 had grade 3 and 12 had grade 4. The difference was significant (P< 0.05). Family was nuclear in 50 and joint in 30. ANC visit was adequate in 35 and inadequate in 45. Period of gestation was term in 32 and preterm in 48. Mothers were anaemic in 55 and normal in 25, 28 mothers had iron and folic acid tablet consumption. The difference was significant (P< 0.05). Conclusion: Authors found that low birth babies had low nutrition status. An association of nuclear family, inadequate ANC visit, preterm, anaemic status of mothers and inadequate iron and folic acid tablet consumption by mothers was found with low- birth weight babies.